2011
DOI: 10.1016/j.jcis.2011.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue from aqueous solution by graphene oxide

Abstract: Graphene oxide (GO) is a highly effective absorbent of methylene blue (MB) and can be used to remove MB from aqueous solution. A huge absorption capacity of 714 mg/g is observed. At initial MB concentrations lower than 250 mg/L, the removal efficiency is higher than 99% and the solution can be decolorized to nearly colorless. The removal process is fast and more efficient at lower temperatures and higher pH values. The increase of ionic strength and the presence of dissolved organic matter would further enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
290
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 632 publications
(318 citation statements)
references
References 37 publications
24
290
1
3
Order By: Relevance
“…Thus, GO definitely has proved to have great potential as an adsorbent. In addition, SRGO performed much better than teak wood bark and activated carbon [29]. It is worth noting that a longer pre-reduction period lessened the adsorption capacity, implying that only a suitable reduction degree would maximize the capacity.…”
Section: Adsorption Of Go-based Materialsmentioning
confidence: 96%
See 4 more Smart Citations
“…Thus, GO definitely has proved to have great potential as an adsorbent. In addition, SRGO performed much better than teak wood bark and activated carbon [29]. It is worth noting that a longer pre-reduction period lessened the adsorption capacity, implying that only a suitable reduction degree would maximize the capacity.…”
Section: Adsorption Of Go-based Materialsmentioning
confidence: 96%
“…Previous work found that methylene blue had a capacity of up to 714 mg g -1 [29]. Thus, GO definitely has proved to have great potential as an adsorbent.…”
Section: Adsorption Of Go-based Materialsmentioning
confidence: 99%
See 3 more Smart Citations